S-BOX CONSTRUCTION IN THE ADVANCED ENCRYPTION STANDARD (AES) DEVELOPMENT ALGORITHM IN GF(2^2), GF(2^4) & GF(2^6) - Setiawan, Adi; Tita, Faldy; Susanto, Bambang (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
This research aims to obtain a method for constructing S-boxes based on GF(22), GF(24) and GF(26). A review of the Galois Field GF(2m) is presented for m=1,2,3,4,5 and 6. Furthermore, it is used to construct an S-box based on GF(22), GF(24) and GF(26). Based on these results, later it can be developed for S-box construction in the AES algorithm which uses the Galois Field GF(2m) for m>=10.